Study of macrodroplet and growth mechanisms with and without ion etchings on the properties of TiN coatings deposited on HSS using cathodic arc physical vapour deposition technique - Mubarak, A.; Hamzah, E.; M. R. M., Toff (Elsevier B V, 2008)
In the present study, titanium nitride (TiN) films were deposited on high-speed steel (HSS) by using cathodic arc physical vapour deposition (CAPVD) technique. The main drawback of this technique, however, is the formation of macrodroplets (MDs) during deposition, resulting in films with rougher morphology. The presence of MDs in CAPVD process is a serious problem during practical tooling applications. The goal of this study was to examine the effect of ion etching with and without titanium (Ti) and chromium (Cr) on the properties of TiN coatings deposited on HSS. Various standard characterization techniques and equipment, such as electron microscopy, atomic force microscopy, hardness testing machine and surface roughness tester, were used to analyze and quantify the following properties and parameters: surface morphology, thickness, adhesion and hardness of the deposited coatings. The coatings deposited with Cr ion etching for 8 and 16 min show half the hardness compared to the samples etched with Ti for similar etching times. Both coating thickness and indentation loads influenced the hardness of the deposited coating. Cr ion etching significantly reduced the surface roughness and hardness compared to Ti ion etching.